Generational differences in healthcare: the role of technology in the path forward - Cecconi, Costanza; Adams, Rob; Cardone, Antonella; Declaye, Joséfine; Silva, Mitchell; Vanlerberghe, Tineke; Guldemond, Nick; Devisch, Ignaas; van Vugt, Joris (Frontiers in Public Health, 2025)
Healthcare systems worldwide are under increasing pressure due to aging populations, rising prevalence of chronic diseases, and heightened patient expectations. Generational differences significantly impact perceptions of health, healthcare decision-making, use of digital technologies, and attitudes toward preventative health. This perspective article explores these differences through the lens of Generational Cohort Theory, focusing on six generations: the Silent Generation, Baby Boomers, Generation X, Millennials, Generation Z, and Generation Alpha. We highlight how each cohort's unique experiences shape their healthcare values, preferences, and engagement with digital health technologies. Younger, tech-savvy generations demand personalized, data-driven healthcare solutions, while older generations often face barriers to adopting digital tools due to limited digital literacy. The article emphasizes the importance of tailoring healthcare delivery, including hybrid care models, to accommodate diverse generational preferences. It further addresses the role of artificial intelligence, wearable technologies, and mobile health apps in preventative care and the need for targeted education to bridge the digital divide and combat misinformation. We propose strategies to integrate digital health solutions and generationally sensitive communication approaches, ensuring equitable access to healthcare services and fostering patient empowerment. Ultimately, this work underscores the need for a multi-faceted, inclusive approach to healthcare delivery to meet the demands of an evolving patient demographic and drive progress in public health systems.